1997
DOI: 10.1029/97gb00223
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pH in the eastern equatorial Pacific across stage 5–6 boundary based on boron isotopes in foraminifera

Abstract: Abstract. Estimates of paleo-pH for the eastern equatorial Pacific Ocean across the oxygen isotopic stage 5-6 boundary have been made based on the boron isotopic composition of planktonic (Orbulina universa) and benthic (mixed species) foraminifera from core V19-28. The estimated deep ocean pH during the penultimate glacial period was about 0.3+0.1 pH units higher compared to the modern deep ocean. This is consistent with previously estimated deep ocean pH changes across the stagel-2 boundary in the western eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 23 publications
4
52
2
Order By: Relevance
“…Furthermore, it is not certain how applicable the calculated isotopic fractionation between the two aqueous species of boron [Kakihana et al, 1977] is to the natural system. In this regard, it is noteworthy that the parallel trend between theoretical trend and the empirical curves suggests that the paleo-pH estimations in previous studies [Sanyal et al, 1995[Sanyal et al, , 1997 …”
Section: Stable Boron Isotope Analysismentioning
confidence: 98%
“…Furthermore, it is not certain how applicable the calculated isotopic fractionation between the two aqueous species of boron [Kakihana et al, 1977] is to the natural system. In this regard, it is noteworthy that the parallel trend between theoretical trend and the empirical curves suggests that the paleo-pH estimations in previous studies [Sanyal et al, 1995[Sanyal et al, , 1997 …”
Section: Stable Boron Isotope Analysismentioning
confidence: 98%
“…Other important B and δ 11 B applications are oceanic crust alteration Spivack et al 1990;Smith et al 1995), environmental pollution (Gabler and Bahr 1999), and pH reconstruction in past oceans (Spivack et al 1993;Sanyal et al 1997;Palmer and Pearson 2003). Recent studies also demonstrate that B and δ 11 B provide crucial information on the study of fluid origin and the degree of water/ sediment interaction at depth, as well as methane hydrates formation (Brumsack and Zuleger 1992;You et al 1993a;You et al 1995You et al 1996Kopf et al 2000;Deyhle and Kopf 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The same is true for pH: Hönisch et al (2008) found that pH in the southeast Atlantic Ocean during the LGM was increased by up to 0.1 pH units above 3500 m water depth, but decreased below that depth (−0.07 pH units). The Pacific may have experienced increases of up to 0.5 pH units (Sanyal et al, 1997). A logical next step would be to apply our model to a combined carbon cycle/general ocean circulation model in order to obtain spatial patterns for δ 13 C foram .…”
Section: Calcification Rate and Comentioning
confidence: 99%